Factors Reducing Pressure Ulcer Risk and the Importance of Care in ALS Patients: A Comprehensive Review - Inoue, Yuriko; Tanaka, Mikako; Ezure, Hiromitsu; Ito, Junji; Sasaki, Akiko; Takaki, Takashi; Hata, Harumi; Takayanagi, Masaaki; Otsuka, Naruhito (British Journal of Healthcare and Medical Research, 2025)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by muscle atrophy, weakness, and loss of motor function. ALS patients are often bedridden for extended periods, increasing their risk of pressure ulcers. However, clinical data suggests that the incidence of pressure ulcers in ALS patients is lower compared to other bedridden patients. This review analyzes the factors contributing to reduced pressure ulcer risk in ALS patients, focusing on "pressure redistribution due to muscle atrophy," "stabilized postures caused by joint contractures," and "comprehensive care provided by caregivers." Additionally, this paper discusses a comprehensive approach to pressure ulcer prevention, including nutritional management, skincare, pressure redistribution techniques, and advanced technologies. Challenges in pressure ulcer prevention and the importance of ALS-specific care are also emphasized.